2004
DOI: 10.1111/j.1440-0960.2004.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial malignant fibrous histiocytoma presenting as recurrent atypical fibroxanthoma

Abstract: Atypical fibroxanthoma (AFX) and malignant fibrous histiocytoma (MFH) are neoplasms of probable fibrohistiocytic lineage. The precise relationship between AFX and MFH remains controversial. We present two cases in which a lesion was excised from the face of an elderly person and reported as AFX. Both cases recurred within 12 months and were reclassified as MFH. They were excised with slow Mohs' micrographic surgery, with adjuvant radiotherapy in one case. In the other, a further recurrence was treated with orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…A differential expression of CD74 by atypical fi broxanthoma and malignant fi brous histiocytoma was reported to distinguish these two lesions, and a weak positivity for CD74 was reported in atypical fi broxanthomas in earlier publications. 1,2,6 It has been reported that atypical fi broxanthoma demonstrates moderate to strong diffuse staining with CD99, in contrast to malignant fi brous histiocytoma, which shows weak and focal immunoreactivity. 7 Our case showed a weak immunoreactivity for CD74 and CD99, and MIB-1 index was about 10%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A differential expression of CD74 by atypical fi broxanthoma and malignant fi brous histiocytoma was reported to distinguish these two lesions, and a weak positivity for CD74 was reported in atypical fi broxanthomas in earlier publications. 1,2,6 It has been reported that atypical fi broxanthoma demonstrates moderate to strong diffuse staining with CD99, in contrast to malignant fi brous histiocytoma, which shows weak and focal immunoreactivity. 7 Our case showed a weak immunoreactivity for CD74 and CD99, and MIB-1 index was about 10%.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Most patients have a long history of sun exposure, and an antecedent trauma is also one of the risk factors. The size of most atypical fi broxanthomas is 1-2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AFX and MFH may have been differentiated based upon positivity for CD74, in which reduced immunoexpression for CD74 in AFX is characterized compared to that in MFH (Lazova R et al 1997). Further examination will be necessary in order to confi rm the reliability of CD74 as a marker with which to differentiate between AFX and MFH (Ly H et al 2004).…”
Section: Afx Is a Unique Entity In Comparison To Mfhmentioning
confidence: 99%